Thoughts on the higher education system in Poland. Changes – issues – evaluation. Part 1 - Grzywacz, Małgorzata; Miłkowska, Grażyna; Piorunek, Magdalena; Sałaciński, Lech (Kultura-Społeczeństwo-Edukacja, 2019)
This report is a part of the results of the international project entitled “Studium in Osteuropa: Ausgewählte Aspekte (Analysen, Befunde)” conducted in the years 2013-2015 under supervision of Prof. Wilfried Schubarth and Dr Andreas Seidl from the Potsdam University, Department of Education Science, and Prof. Karsten Speck from the University of Oldenburg, Germany. The project was conducted jointly by representatives of academic centres from Germany, the Czech Republic, Poland and Russia. Its general aim was a comparative analysis of the effects of implementation of Bologna Process directives into the higher education systems of the individual countries. The changes introduced into the higher education systems in the countries involved in the project were described and evaluated, discussed was in particular the problems of education of teachers at the university level. The following text is the result of the contribution of the Polish group participating in the project. The report will be presented in two parts. The first part is focused on the macro-societal context of transformations in the higher education system in Poland. The implementation of selected aspects of Bologna Process directives is described and supplemented by empirical comments. The second part deals with selected aspects of university level education of teachers, followed by a polemic against the assumptions and execution of the target transformations of higher education system.